Mouthwashes: Implications for Practice - Zoë L.S. Brookes; Michael McCullough; Purnima Kumar; Colman McGrath (Elsevier, 2023)
ABSTRACT: This is the concluding article in the supplement on the role of mouthwashes in oral care, which summarises the current guidelines across the globe regarding their acceptable adjunctive use for managing caries, gingivitis, and periodontal disease. Based on moderate evidence for clinical effectiveness, most current guidelines suggest fluoride mouthwashes for the management of dental caries, and chlorhexidine for the management of periodontal diseases. However there still appears to be gaps in the literature underpinning these recommendations. Importantly, all evidence supports such mouthwash use "adjunctively," alongside mechanical oral hygiene measures. Other antimicrobial mouthwashes such as essential oils and cetylpyridinium chloride may also be clinically effective against plaque and gingivitis, but there is a current lack of robust evidence of natural mouthwashes to recommend their adjunctive use. The authors of the current review are of the view that mouthwashes may not be of much value in those with good periodontal health or low caries risk. The reasons for this are, the potential i) risks of allergic reactions, ii) dysbiosis of the oral microbiota, iii) emergence of antimicrobial resistance, and iv) deleterious effects on the environment. There is, however, much empirical research needed on mouthwashes, particularly in vivo research derived through clinical trials. Thus, dental practitioners need to keep abreast of the evidence base on the current, and the emerging, over-the-counter mouthwashes, and pay heed to the consensus views emanating from systematic reviews, as well as international guidelines on mouthwashes.